2021
DOI: 10.1007/s11240-021-02173-5
|View full text |Cite
|
Sign up to set email alerts
|

L-phenylalanine applications and culture duration affect root growth and production of tropane alkaloids and phenolics in adventitious root cultures of Hyoscyamus niger L.

Abstract: This study was aimed to determine the effects of different concentrations of L-phenylalanine (0.25, 0.50 and 1.00 mM L-Phe) applied to adventitious root cultures for different culture durations on root growth and production of tropane alkaloids and phenolics in Hyoscyamus niger. For this purpose, adventitious roots obtained from petiole explants of in vitro seedlings were used as plant materials. After adventitious roots were cultured in liquid MS medium, L-Phe was applied to the adventitious roots. Then the r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Seed germination and adventitious root collection followed the methods described in detail in our previous study (Demirci et al, 2022). Briefly, seeds treated with gibberellic acid for 48 hours were rinsed with double distilled water (ddH2O) and then sterilized by shaking with 70% ethanol (%99, Tekkim, Turkey) for 10 seconds and with 0.1% mercury chloride (HgCl2, Sigma-Aldrich, Germany) for 10 min.…”
Section: Obtaining Adventitious Rootsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seed germination and adventitious root collection followed the methods described in detail in our previous study (Demirci et al, 2022). Briefly, seeds treated with gibberellic acid for 48 hours were rinsed with double distilled water (ddH2O) and then sterilized by shaking with 70% ethanol (%99, Tekkim, Turkey) for 10 seconds and with 0.1% mercury chloride (HgCl2, Sigma-Aldrich, Germany) for 10 min.…”
Section: Obtaining Adventitious Rootsmentioning
confidence: 99%
“…Culture time is another important factor determining yield in the in vitro production of plant SMs (Demirci et al, 2020;Demirci et al, 2021;Demirci et al, 2022;Narayani and Srivastava 2017). In nature, each SM reaches its highest level at different time periods (Figueiredo et al, 2008;Soni et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies revealed that the duration of cultivation on the inducing medium also affects the content of secondary metabolites and their qualitative composition in the in vitro AR culture. The dependence of tropane alkaloid and phenol accumulation on the duration of cultivation and L-phenylalanine treatment in the in vitro AR culture of Hyoscyamus niger L. was shown [52]. The effect of the culture period on the yield of secondary metabolites with an optimal 15-day period is shown in the in vitro AR of Hyoscyamus niger L. [53].…”
Section: In Vitro Adventitious Roots Culturementioning
confidence: 97%